Study of Downstream Analysis of Strategic Investment in Petroleum Commodities In Increasing the Value of Indonesian Petroleum Products - Bhagya, Tombak Gapura; Yasmadi, Bambang; Yulianti, Dini; Prakarsa, Graha; Anggraito, Hendry (Universitas Insan Cendekia Mandiri, 2024)
The government is currently trying to increase the added value of product, especially products whose raw material come from within the country. One way to increase added value is by downstreaming commodities. Petroleum is one of the commodities that will be downstream from the upstream to downstream sector. There is limited petroleum in Indonesia, so it needs to be utilized as best as possible. So that the added value of petroleum can be returned with greater value. From the results of the study, there are five industrial sectors that can be developed by government to downstream petroleum commodities, namely liquid parafin, phenol, cumene, caprolacton and polycarbonate